An analysis of factors contributing to the severity of academic cheating behavior among university students—A case of Hefei city - Yongnian Cao; Ali Khatibi; Jacquline Tham (Environment and Social Psychology, 2025)
The aim of this study was to investigate the causes of academic cheating among university students at a university in Hefei, Anhui Province. 642 general students from Accounting, Finance and Architecture were randomly selected from a university, and data were collected by distributing questionnaires. To collect the data, a questionnaire was used that included the socio-demographic characteristics of the participants and relevant cheating factors. The results of the study highlighted factors related to the students themselves, factors related to teachers and factors related to peers. The questionnaire used to collect data included both socio-demographic characteristics of the students and factors influencing cheating, and the study found that despite the majority of respondents perceiving the seriousness of cheating, they continued to actively engage in cheating behavior. This paper analyzes the factors affecting the severity of cheating among college students by questionnaire survey and data collection, and uses SPSS and AMOSS technology.